Group Differences in Learning between Students and Employees - Tjitra, Hora W.; Zhang, Yang (Faculty of Psychology, Universitas Surabaya, 2007)
Our research focuses on learning styles and experiences and preferences for learning me- thod and media in the Chinese cultural context. Based on 302 questionnaires collected from three group—Employees, graduate students, and undergraduate students, we found that the dominant Chi- nese learning style is “Diverging” and then “Assimilating”, based on Kolb’s (1984) theory of learning styles. Learning style is stable across different demographic groups in our sample, including gender, occupation, major, and educational experience. We also found that there was a higher level of consis- tency between frequency and preference for learning media and methods in employee group than for graduate student group and for undergraduate student group. Cross-group comparison showed that there is little difference in preference for learning method and media across three groups; however, in terms of experiences (i.e., frequency of use), there is a higher degree of differences across the three groups, with employees reporting a wider range and more frequent use in general. Possible explana- tions will be discussed. Penelitian kami terfokus pada gaya belajar dan pengalaman serta pilihan metode dan media belajar dalam konteks budaya China. Berdasarkan 302 kuesioner yang dikumpulkan dari 3 kelom- pok—karyawan, mahasiswa S-2, dan mahasiswa S-1, kami menemukan bahwa berdasarkan teori Kolb (1984) gaya belajar China yang dominan adalah “menyimpang” dan kemudian “mengasimilasi.” Gaya belajar pada sampel kami cukup stabil lintas kelompok demografik yang berbeda, termasuk gender, pekerjaan, pilihan utama (major) dan pengalaman pendidikan. Kami juga menemukan adanya tingkat konsistensi yang tinggi antara frekuensi dan pilihan media dan metode belajar pada kelompok pekerja daripada pada kelompok mahasiswa S-2 dan S-1. Perbandingan lintas-kelompok menunjuk- kan bahwa terdapat sedikit perbedaan dalam pilihan metode dan media belajar lintas ketiga kelompok tersebut; namun, dalam kaitan pengalaman (misalnya frekuensi penggunaan), terdapat derajat perbe- daan yang lebih tinggi lintas ketiga kelompok, yaitu para pekerja melaporkan rentang yang lebih lebar dan secara umum lebih sering menggunakan metode dan media. Dibahas berbagai kemungkinan pen- jelasannya.